To find the equation of the new line after translating the original line \( y = 3x + 2 \) one unit to the right and two units up, we can follow these steps:
-
Translation to the right: When we translate a line to the right by \( h \) units, we replace \( x \) with \( x - h \). In this case, \( h = 1 \), so we replace \( x \) with \( x - 1 \).
The equation becomes: \[ y = 3(x - 1) + 2 \] Simplifying this gives: \[ y = 3x - 3 + 2 = 3x - 1 \]
-
Translation up: Now, we need to translate the line up by \( k = 2 \) units. This means we add \( k \) to \( y \): \[ y = 3x - 1 + 2 \] Simplifying gives: \[ y = 3x + 1 \]
Thus, the equation of the new line after the translation is: \[ \boxed{y = 3x + 1} \]